2012
DOI: 10.5539/jas.v4n12p59
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation and Autoclave Sterilization Peat and Compost as the Carrier for Rhizobial Inoculant Production

Abstract: Rhizobium is a biofertilizer for leguminous crops. To formulate this form of fertilizer, the suitable sterilization processes of carrier are important. Therefore, the aim of this research was to elucidate the process of gamma irradiation and autoclaving on peat and compost based carriers for rhizobial inoculant production. Carriers with 10% moisture content packing in polyethylene bag could be efficiently sterilized by irradiation at 10-20 kGy, or by autoclaving with tyndallization approach (autoclaving two ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Namun metode ini dapat merubah karakter kimia dan fisik bahan pembawa yang pada akhirnya akan berpengaruh pada populasi mikrob di dalamnya. Iradiasi sinar gamma Co-60 lebih mudah, dapat digunakan dalam skala besar, dan dapat memperpanjang masa simpan [19,20]. Tujuan penelitian ini adalah untuk mempelajari pengaruh sterilisasi menggunakan sinar gamma Co-60 dan autoclave terhadap sifatsifat bahan pembawa, populasi mikrob fungsional, dan pengaruhnya terhadap pertumbuhan dan produksi kedelai varietas Mutiara 3.…”
Section: Pendahuluanunclassified
“…Namun metode ini dapat merubah karakter kimia dan fisik bahan pembawa yang pada akhirnya akan berpengaruh pada populasi mikrob di dalamnya. Iradiasi sinar gamma Co-60 lebih mudah, dapat digunakan dalam skala besar, dan dapat memperpanjang masa simpan [19,20]. Tujuan penelitian ini adalah untuk mempelajari pengaruh sterilisasi menggunakan sinar gamma Co-60 dan autoclave terhadap sifatsifat bahan pembawa, populasi mikrob fungsional, dan pengaruhnya terhadap pertumbuhan dan produksi kedelai varietas Mutiara 3.…”
Section: Pendahuluanunclassified
“…This showed that the heat from water vapor by an autoclave unable to penetrate the carrier matrix and thus unable to eliminate bacterial growth. This also occurred in another study which employed autoclaving with tyndallization approach on peat and compost [5]. However, different results occurred in the carrier in the form of peat moss, the mixture of peat moss plus vermiculite, wheat bran, rice husk, clay, and sodium alginate, sterilized by autoclave as well, that no contaminants have been detected in all the sterilized carriers [14].…”
Section: B Elimination Of Microorganisms After Sterilizationmentioning
confidence: 95%
“…The gammairradiation sterilization method at a dose of 25 kGy is able to sterilize the carrier material until the microorganism is not detected. Gamma ray is an effective method for sterilization, since the ionizing radiation interacts directly with charged particles such as DNA, and results in doublestrand break [5]. In contrast to sterilization with gammairradiation, autoclave sterilization left microorganisms, especially bacteria, with different concentrations according to the carrier composition.…”
Section: B Elimination Of Microorganisms After Sterilizationmentioning
confidence: 99%
See 2 more Smart Citations